Poverty in India : research and policy - Harriss-White, Barbara, 1946-; Guhan, Sanjivi; Cassen, Robert (Bombay ; New York : Oxford University Press, New York, 1992)
Papers presented at a workshop held at Queen Elizabeth House, Oxford in October 1987.
Includes bibliographical references and index.
Keywords: Poor -- Research -- India; Poor -- Government policy -- India